Addressing difficulties in literacy development : responses at family, school, pupil, and teacher levels - Wearmouth, Janice; Soler, Janet; Reid, Gavin, 1950- (RoutledgeFalmer : Open University : University of Edinburgh, 2002)
"This book will be of interest to postgraduate students, teachers, researchers, education professionals and policy makers who are looking for well-researched, practical strategies to address difficulties in literacy development."--Jacket